Corporate and Financial Strategies of Abhishek Industries Ltd.: A Listed Textile Company of Punjab - Gupta, Sheenu; Singh, Gurcharan (Indian Journal of Finance, 2015)
The financial success of any company can be attributed to powerful strategies. Long time financial strategies showcase the planning and work-culture being practiced by various companies with respect to their competitors. The present study related and referred to the financial strategies of Abhishek Industries Ltd. (now named as Trident Group) through analysis of its financial data for 10 years (1999-2010). The main objective of the study was to assess the performance of Abhishek Industries Ltd. by using analytical financial tools that can provide an insight into the financial competence of the company and aided in understanding the strengths and weaknesses pertaining to its financial strategies.